Clinical manifestations and outcomes of respiratory syncytial virus infection in children less than two years in Colombia - Buendía, JA; Polack, FP; Patiño, DG (Springer, 2020)
This retrospective study describes the epidemiology and risk factors associated with severe complications in lower respiratory tract infection (LRTI) due to respiratory syncytial virus (RSV) in a population of infants hospitalized in a tertiary care hospital in a tropical region of Colombia. RSV was detected in 193 (46.3%) of 417 patients with LRTI. The average hospital stay lasted for 5.9 days. Severe hypoxemia (SpO2 ≤90% in the emergency department) was present in 57.5% of the patients. After controlling for potential confounders, comorbidities bronchopulmonary dysplasia, congenital heart disease, length of hospital stay, and alveolar infiltrates in X-ray were independent predictors of severe complications in RSV LRTI.